RAB18 Loss Interferes With Lipid Droplet Catabolism and Provokes Autophagy Network Adaptations. Issue 4 (14th February 2020) - Bekbulat, Fazilet; Schmitt, Daniel; Feldmann, Anne; Huesmann, Heike; Eimer, Stefan; Juretschke, Thomas; Beli, Petra; Behl, Christian; Kern, Andreas
Abstract: Autophagy is dependent on appropriate lipid supply for autophagosome formation. The regulation of lipid acquisition and the autophagy network response to lipid-limiting conditions are mostly elusive. Here, we show that the knockout of the RAB GTPase RAB18 interferes with lipid droplet catabolism, causing an impaired fatty acid release. The resulting reduced lipid-droplet-derived lipid availability influences autophagy and provokes adaptive modifications of the autophagy network. These adjustments include increased expression and phosphorylation of ATG2B as well as augmented formation of the ATG12-ATG5 conjugate. Moreover, ATG9A shows an enhanced phosphorylation at amino acid residues tyrosine 8 and serine 14, resulting in an increased ATG9A trafficking. Via pharmacological inhibition of Y8 phosphorylation, we demonstrate that this ATG9A modification is important to maintain basal autophagy under RAB18 knockout conditions. However, while the network adaptations are sufficient to maintain basal autophagic activity, they are incapable of ensuring autophagy induction upon starvation, which is characterized by an enhanced lipid demand. Thus, here, we define the molecular role of RAB18 in connecting lipid droplets and autophagy, emphasize the significance of lipid droplets as lipid sources for the degradative pathway, and uncover a remarkable autophagy network plasticity, including phosphorylation-dependent ATG9A activation, to compensate reduced lipid availability in order to rescue basal autophagic activity. Graphical abstract: Image 1 Highlights: The knockout of RAB18 impedes lipid droplet catabolism. Insufficient LD-derived lipid availability affects autophagy. The autophagy network adapts to maintain autophagic activity. Prominent adaptations include enhanced ATG9A phosphorylation. Increased ATG9A trafficking rescues basal autophagy under lipid-limiting conditions.